2016
DOI: 10.1016/j.enbuild.2016.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approach for the life cycle multi-objective optimization of buildings combining objective reduction and surrogate modeling

Abstract: We present a systematic approach to optimize the thermal insulation of a building.  The optimization reduces simultaneously the cost and several environmental impacts.  We resort to an objective reduction method to simplify the problem resolution.  We built a surrogate model to expedite the search for Pareto optimal solutions.  Significant improvements compared to the base case (no insulation) are achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 48 publications
(55 reference statements)
1
19
0
1
Order By: Relevance
“…Introducing additional parameters, constraints, and value choices will lead to more complex models. Carreras et al [47] showed how multiobjective optimisation can be used as a tool to study trade-off solutions, using nonlinear programming to identify redundant environmental metrics. The approach allows a simplification of multicriteria problems, reducing the computational time to identify the best options.…”
Section: Methodsmentioning
confidence: 99%
“…Introducing additional parameters, constraints, and value choices will lead to more complex models. Carreras et al [47] showed how multiobjective optimisation can be used as a tool to study trade-off solutions, using nonlinear programming to identify redundant environmental metrics. The approach allows a simplification of multicriteria problems, reducing the computational time to identify the best options.…”
Section: Methodsmentioning
confidence: 99%
“…Although GAs do not guarantee finding the global optimum, they have become advanced optimization tool for a wide range of problems. GAs were further applied in a number of the papers quoted in the introduction of this paper [2,5,14,15,[29][30][31][32][33]35,36,38,[40][41][42].…”
Section: Optimization Algorithmmentioning
confidence: 99%
“…The optimization of the insulation thickness of a house considering both economic and environmental concerns is presented by Carreras et al [36]. The authors proposed a systematic framework for the design of buildings that combines a rigorous objective reduction method with a surrogate optimization model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hybrid genetic algorithm and artificial neural net-works was used for the optimization. The optimization of the insulation thickness of a house considering both economic and environmental (eco-indicator 99 methodology) concerns is presented by Carreras et al [33]. The authors proposed a systematic framework for the design of buildings that combines a rigorous objective reduction method with a surrogate optimization model.…”
Section: Introductionmentioning
confidence: 99%